In vivo Evaluation of Saccharomyces-Modified Tempeh as Potential Prebiotic and Probiotic Food using Mus musculus as an Animal Model - Maria Erna Kustyawati; Tegar Suryawan; Samsul Rizal; Esa Ghanim Fadhallah; Khairun Nisa Berawi (Journal of Multidisciplinary Applied Natural Science, 2025)
Saccharomyces-modified tempeh (SM tempeh), which is produced by adding Saccharomyces cerevisiae during soybean fermentation, is considered to have the potential as a source of prebiotics. The research aims to determine the prebiotic activity score (PAS) of SM tempeh extract against the probiotics S. cerevisiae and Lactobacillus casei, as well as to evaluate the resistance of S. cerevisiae and Escherichia coli in the intestines of mice fed tempeh. The PAS evaluation was carried out using a factorial complete randomized block design with three replications and one-way ANOVA for data analysis followed by the least significant difference test (5%). Meanwhile, microbial survivability was carried out in vivo using male Mus musculus strain mice fed standard feed, and standard feed with tempeh extract supplementation. The results showed that the supplemetation of either SM or commercial tempeh extract to the growth media significantly affected on the microbial load of S. cerevisiae, L. casei and E. coli, but the concentrations of tempeh extract had no significant effect. Apart from that, the concentrations of tempeh extract had no effect on the PAS of S. cerevisiae and L. casei, meaning that it was able to promote the growth of probiotics in the amount added to the media in the range of 2–10%. In addition, the feeding type had a significant effect on the survival of S. cerevisiae and E. coli in the intestines. S. cerevisiae carried on SM tempeh was detected surviving in the mice intestine at a rate of 6.12 log CFU/g, indicating that the tempeh was a probiotic food. Most likely SM tempeh is a synbiotic food.